WATER ABSORPTION AND WATER RESISTANCE OF HYDROIZOL-K WATERPROOFING MATERIAL (Scientific journal of the Fergana State University, 2024)
Hydroizol-K waterproofing material is tested according to two standard requirements: water absorption and water resistance of the material. The results of testing the samples of Gidroizol-K waterproofing material are given. The graph of water absorption of the samples of Gidroizol-K waterproofing material with a thickness of 3 mm, 5 mm and 10 mm is presented. The water absorption rate of the Gidroizol-K waterproofing material sample with a thickness of 5 mm was proven to be the best compared to other samples and was 0.59%. In accordance with GOST 8625-77, based on the test results, it was determined that the water resistance of Gidroizol-K waterproofing material samples had no traces of water on the surface of the three samples.